Quench and self-protecting behaviour of an intra-layer no-insulation (LNI) REBCO coil at 31.4 T. (30th April 2021) - Suetomi, Y; Yoshida, T; Takahashi, S; Takao, T; Nishijima, G; Kitaguchi, H; Miyoshi, Y; Hamada, M; Saito, K; Piao, R; Takeda, Y; Maeda, H; et al.
Abstract: This paper presents experimental results on a quench of an intra-layer no-insulation (LNI) (RE: rare earth)Ba2 Cu3 O7− δ (REBCO) coil in a 31.4 T central magnetic field and simulated results on the quench. We have been designing a persistent-mode 1.3 GHz (30.5 T) nuclear magnetic resonance (NMR) magnet with a layer-wound REBCO inner coil. Protection of the REBCO coil from quench is a significant issue and the coil employs the LNI method to obtain self-protecting characteristics. We conducted high-field generation and quench experiments on an LNI-REBCO coil connected to an insulated Bi2 Sr2 Ca2 Cu3 O x (Bi-2223) coil under a background magnetic field of 17.2 T as a model of the 1.3 GHz NMR magnet. The coils successfully generated a central magnetic field of 31.4 T. Although the LNI-REBCO coil quenched at 31.4 T, this quench did not cause any degradation to the coil. A numerical simulation showed the current distribution during the quench was non-uniform and changed rapidly over time due to current bypassing through copper sheets between layers, resulting in faster quench propagation than in an insulated REBCO coil. During the quench propagation, the peak temperature ( T peak ) and the peak hoop stress Bz JR ( σθ, peak ) were calculated to be 330 K and 718 MPa, respectively. These are below critical values that cause degradation. The simulation also showed that the high electrical contact resistivity ( ρ ct ) of 10 000 µ Ω cm 2, between REBCO conductors and copper sheets in the LNI-REBCO coil winding, played an important role in protection. When ρ ct was as low as 70 µ Ω cm 2, the quench propagation became too fast and large additional currents were induced, resulting in an extremely high σθ, peak of 1398 MPa, while the T peak was as low as 75 K. In short, the high ρ ct in the present coil caused a high T peak, but succeeded in suppressing σθ, peak and protecting the coil from the quench.